Proof-of-concept study for an enhanced surrogate marker of endothelial function in diabetes - Goh, S. (2018)
Diabetes mellitus affects distal small vessels earlier and to a greater extent than proximal vessels. Vascular disease starts from activation of the endothelial cells, which if prolonged may lead to reduced distensibility of the vessel when maximally stimulated. Hence a device which measures distensibility of a distal vessel should be a good biomarker for subclinical disease. We have developed a device capable of measuring reactive hyperaemia induced changes in the radial artery flow, volumetric changes and accompanying effects on the vessel wall. The measurement is based on the magnetic flux disturbance upon haemodynamic modulation as blood flows through a uniformly applied magnetic field, and generates what we have termed the radial artery maximum distensibility index (RA-MDI). In a proof-of-concept study we found significant correlations between RA-MDI and cardiovascular risk factors, scoring systems and carotid artery intima-media thickness. Further large scale prospective studies need to be conducted to ascertain the correlations with cardiovascular events.